Evaluation of fluid rheology and pore space characteristics in the inner and external cake formation in overbalanced drilling operations - Santos, Nara Brandão Costa (2021)
Essa tese foi desenvolvida em parte na University of Kansas (EUA) através dos fomentos UFU/CapesPrInt (88881.311515/2018-01) e American Chemical Society Petroleum Research Fund (ACS PRF#59089-DNI9) .